2018
DOI: 10.1371/journal.pmed.1002586
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated burden and mitigation of carbon-dioxide-induced nutritional deficiencies and related diseases: A simulation modeling study

Abstract: BackgroundRising atmospheric carbon dioxide concentrations are anticipated to decrease the zinc and iron concentrations of crops. The associated disease burden and optimal mitigation strategies remain unknown. We sought to understand where and to what extent increasing carbon dioxide concentrations may increase the global burden of nutritional deficiencies through changes in crop nutrient concentrations, and the effects of potential mitigation strategies.Methods and findingsFor each of 137 countries, we incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 23 publications
(39 reference statements)
1
24
0
Order By: Relevance
“…These findings build on previous modeling work [14,15] to quantify the inequalities in the nutritional impacts of climate change and add to our understanding of climate justice. This work shows that the countries and people that have contributed the least to global rising CO 2 emissions are likely to be at the greatest risk of increased zinc and protein inadequacy and underscores the need for substantial greenhouse gas mitigation and adaptation efforts and also greater attention to redressing such injustices across countries.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…These findings build on previous modeling work [14,15] to quantify the inequalities in the nutritional impacts of climate change and add to our understanding of climate justice. This work shows that the countries and people that have contributed the least to global rising CO 2 emissions are likely to be at the greatest risk of increased zinc and protein inadequacy and underscores the need for substantial greenhouse gas mitigation and adaptation efforts and also greater attention to redressing such injustices across countries.…”
Section: Discussionsupporting
confidence: 64%
“…A full description of their methods may be found in the original publication, but the following is a brief summary [14]. Previous studies [10][11][12]14,15] have found that an elevated CO 2 concentration of 550 ppm can reduce the zinc and protein content of many staple crops by up to 17% relative to ambient conditions of 363-386 ppm. Based on our current global emissions trajectory, we will reach 550 ppm CO 2 by roughly mid-century [13].…”
Section: Increased Prevalence Of Dietary Zinc and Protein Inadequacy mentioning
confidence: 99%
See 1 more Smart Citation
“…C3 plants make up >95% of plant species, provide >75% of calories to humans, and include rice, wheat, and nearly all crop fruits and vegetables . CO 2 ‐induced declines of 5–15% in protein, iron, and zinc in edible parts of C3 crops have been reported, and are projected to waste over 125 million disability‐adjusted life years (DALYs) by 2050 …”
Section: Introductionmentioning
confidence: 99%
“…The need for a Centre such as CFF arises for several reasons but not least because human food systems are currently dominated by four crops-rice, wheat, maize and soybean-of which the three cereals provide over 50% of plant-based human food (IPES-Food 2016). In a warming world with more extreme weather, reliance on such a limited number of crops poses major challenges to food and nutritional security (Kahane et al 2013;Weyant et al 2018). Furthermore, existing deficiencies of key vitamins and minerals pose a serious constraint to human health and economic development (GLOPAN 2016).…”
Section: Cff's Remit and Research Objectivesmentioning
confidence: 99%